Farmer's participation in a pump irrigation project : a case study in Haurgeulis, Indramayu, West Java - Budhi, Gelar Satya (2003)
The primary purpose of the study is to examine farmers' participation in the Persaluan Pelani Pemakai Air (P3A) pump irrigation project in Sub-district (Kecamatan) Haurgeulis of District (Kabupalen) Indramayu in West Java, Indonesia. The specific objectives are: 1) to study the origin and organisation of the P3A pump irrigation project; 2) to examine actual participation in the planning and implementation of the project; 3) to identify factors influencing payment of irrigation service fees; and 4) to identify the obstacles encountered in encouraging farmers to participate in the project. This study uses two approaches, qualitative (for Objective One, Two, and Four) and quantitative (for Objective Tree). Three data collection techniques were applied, namely: survey, in-depth interview, and direct observation. Survey technique was used to get representative quantitative data obtained from farmers who were selected randomly. In-depth interview with farmers was to obtain information on the implementation of the P3A pump irrigation project including their role in the activities of the project, while in-depth interview with informants was to get confirmation of project implementation, in general, and to obtain information related to every agency involved. Direct observation was employed to obtain information on the situation of the desas including physical description and farmer' behaviour. The study showed that, in general, farmers' participation in the pump irrigation project was low both in the planning or implementation stages. In both activities the farmers did not show strong willingness although there were some bodies that supported them with loans and technical assistance in running the project. Their participation also remained low although the YBSD encouraged the farmers to involve them at most activities. Their participation could not even appear strong despite the emergence of a mobiliser who struggled to build pump irrigation. Although the initiative to build pump irrigation came from farmers, they could not commit their wish by not involving themselves all the way. There were some reasons why farmers' participation was low. The main reason was addressed to the existence of some obstacles related to it. There were three sources of obstacles that impeded farmers' participation, namely those that came from the project recipients, poor encouragement from local leadership, and the weakness of the implementing committee. The next reason for low participation was the low education level of the farmers, since the study found out that the lower the education level the farmers had, the lower their participation would be. In fact, most farmers were not even educated. On the other hand, small land farmers were not strong enough to raise participation although the study results showed that the small farmers had the potential to do so. This was because the small farmers faced hard challenges to raise their participation since factors that impeded participation were too strong to overcome.